(untitled) (ModaPalavra e-periódico, 2017)
Clothing is an object that is in direct contact with the body, and when poorly designed can limit the individual in the daily activities, thus considering the usability of the product. This article aims to highlight the analysis of user tasks during the development of the fashion product design, showing in which steps the knowledge of movements performed by man shall be inserted. By showing stages, from research and creation until modeling, at which begins the construction of the product, it is remarkable the influence of ergonomics and anthropometry in the process, and the knowledge of the human body in its entirety is essential for the construction of clothing. For this, a literature review was performed to unite the concepts necessary to achieve the objective of the work. The subjects covered are intended to educate the fashion designer as understanding the user’s activities will influence the quality of the designed product.